PENYESUAIAN DIRI DAN DUKUNGAN KELUARGA DENGAN KEPRIBADIAN TANGGUH SANTRIWATI TAHUN PERTAMA PONDOK PESANTREN X CIKARANG: PENYESUAIAN DIRI DAN DUKUNGAN KELUARGA DENGAN KEPRIBADIAN TANGGUH SANTRIWATI TAHUN PERTAMA PONDOK PESANTREN X CIKARANG - Oktaviani, Ellsa Azma; Indrawati, Erdina (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2018)
ABSTRACT This study aims to determine the relationship between personal adjustment and family support with hardiness in first year students of X Islamic Boarding School in Cikarang. Research uses quantitative methods. The sampling technique of this study uses proportional random sampling with a sample of 135 students. Data retrieval uses a Likert scale consisting of, hardiness scale, personal adjustment scale and family support scale using SPSS 22.00 for windows. The result of bivariate correlation technique analysis shows that there is a significant relationship with the positive direction between personal adjustment and hardiness, the correlation coefficient value (rxy1 ) is 0.712 with p = 0.000 (p <0.05), and there is a significant relationship with the positive direction between support family with hardiness obtained correlation coefficient value (rxy2 ) of 0.433 with p = 0.000 (p <0.05). To test the hypothesis with multivariate correlation technique, R value is 0.725 which means that there is a significant relationship with the positive direction between personal adjustment and family support with hardiness. The effective contribution between personal adjustment and family support is 52.5% while the remaining 47.5% is a contribution other factors not examined.